Synthesis of Anatase/Brookite Mixed Phase TiO2 Nanostructures and its Photocatalytic Performance Study. Issue 33 (6th September 2021) - Jawale, Niteen S.; Arbuj, Sudhir S.; Umarji, Govind G.; Rane, Sunit B.
Abstract: The TiO2 nanostructures were prepared using hydrothermal reaction technique at different reaction temperatures viz., 120 °C, 160 °C, and 200 °C for 24 h. The synthesized TiO2 nanostructures was characterised by various spectroscopic techniques. XRD indicate the formation of highly crystalline nano size particles of anatase phase of TiO2 along with minor percentage of brookite phase. Diffuse reflectance UV‐Visible spectroscopy depicts the band gap around 3.2 eV. The FE‐SEM shows formation of spherical particles having size in the range of 5 to 10 nm, however the small particles tend to agglomerate leading to the formation of submicron size clusters. TEM analysis confirms the formation of nanostructured TiO2 having size in the range of 5 to 10 nm with distorted spherical shaped morphology. The photocatalytic performance of the synthesized TiO2 was investigated by observing the degradation of aqueous methylene blue (MB) dye and H2 generation via water splitting under 400 W mercury vapour lamp respectively. Among the prepared samples, the TiO2 prepared at 160 °C, showed highest MB degradation (97 %) within 1 h of irradiation time. The photocatalytic H2 generation via water splitting was also investigated and found to be highest for TiO2 prepared at 160 °C, the observed rate of H2 generation was 3848 μmol/0.1 g in 4 h is almost twelve fold higher than the pure anatase phase. Abstract : The mixed phases of TiO2 nanostructures such as anatase and brookite were hydrothermally synthesized and studied its photocatalytic H2 generation performance. Almost twelve fold enhancement in the H2 generation is observed with the mixed phase of TiO2 than pure anatase phase.